The Dilemma of Factor Allocation and Wage Difference under the Constant Region-Wide Returns to Scale - Xi Xi; Yuanyuan Gong; Runze Yuan (Discrete Dynamics in Nature and Society)
In the model setting of multiregional macroeconomic research, the constant return on scale of all production functions and the free flow of all production factors cannot be combined. Otherwise, the potential theoretical conflict, that is, the problem of contradiction equations, may arise. If there is a unified capital interest rate in the market and the return on scale of production in all regions remains unchanged, it is necessary to set restrictions on the flow of labor force in order to realize the differential wages among regions. When the interest rate is not too high, the regional wage increases with the larger output capital elasticity.